A Rare Case of Malbranchea Species Pulmonary Infection in the Setting of Suspected Selective Immunoglobulin M Deficiency. Issue 1 (January 2019) - Espinosa, Ronald F.; Pyun, John; Modena, Brian D.; Crum-Cianflone, Nancy
Abstract : Abstract: Humoral immunodeficiencies are traditionally associated with prolonged and recurrent respiratory tract infections, including unusual pathogens. We describe a case of a 63-year-old man with a history of chronic obstructive pulmonary disease and recurrent pneumonias (including Pseudomonas ) who presented with cough, dyspnea, and respiratory failure with computed tomography imaging showing bilateral consolidations and cavitary lesions. The bronchoalveolar lavage fungal culture grew Malbranchea species, whereas viral, bacterial, and mycobacterial cultures were negative. Because of multiple hospitalizations for pneumonia and the presence of this unusual pathogen, quantitative immunoglobulin levels were obtained, revealing an undetectable total immunoglobulin M (IgM) level (<5 mg/dL) with normal levels of IgG (1270 mg/dL) and IgA (108 mg/dL). Complete blood count with differential and lymphocyte subsets (ie, CD4, CD8) showed no deficiency in immune cell counts, and human immunodeficiency virus antibody/antigen testing was negative. The patient improved clinically after antifungal therapy with posaconazole, and he additionally received prophylactic inhaled tobramycin given his history of recurrent pulmonary infections and suspected selective IgM deficiency.